American Missionaries in Revolutionary Russia - Ginzburg, Lyubov (Journal of Russian American Studies, 2017)
This article presents a case study in public diplomacy through the history of American Methodists in St. Petersburg spanning an era of unprecedented social and political turmoil and strife. In particular, it features the story of American pastor George Albert Simons, who was involved in missionary and charitable activities in Russia’s northern capital throughout the course of WWI, the revolutions, and their immediate aftermath. Among other primary sources, the author has referenced a bilingual newsletter of the American colony Christian Advocate, the most complete collection of which is in the National Library of Russia in St. Petersburg, and materials from the United Methodist Church Archives in New Jersey, some of which have not been previously published.